1995
DOI: 10.1099/00207713-45-2-334
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Study of Bacteria Isolated from Plants: Proposal of Sphingomonas rosa sp. nov., Sphingomonas pruni sp. nov., Sphingomonas asaccharolytica sp. nov., and Sphingomonas mali sp. nov.

Abstract: The taxonomic positions of 10 strains of 3-ketolactose-forming bacteria which were isolated from the roots of plants (Rosa sp., Psychotria nairobiensis, Ardisiu crispa, Prunus persica, and apple trees) were investigated. The DNA base compositions of these strains ranged from 64.0 to 65.7 mol%, the isoprenoid quinone of each strain was ubiquinone 10,3-hydroxy fatty acids were lacking in the cellular fatty acids of these organisms, and all of the strains contained a sphingolipid with the long-chain base dihydros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(77 citation statements)
references
References 17 publications
8
67
0
2
Order By: Relevance
“…They possess ubiquinone-10 (Q-10) as the major respiratory quinone. From literature, we also confirmed that all type strains in Group 4 in the alpha-subclass of Proteohacteria possess ubiquinone-10 (Q-10) as the major respiratory quinone (1,7,8,10,17,18,21,25,26,33,34,(36)(37)(38). …”
Section: Phenotypic Characteristicssupporting
confidence: 57%
See 2 more Smart Citations
“…They possess ubiquinone-10 (Q-10) as the major respiratory quinone. From literature, we also confirmed that all type strains in Group 4 in the alpha-subclass of Proteohacteria possess ubiquinone-10 (Q-10) as the major respiratory quinone (1,7,8,10,17,18,21,25,26,33,34,(36)(37)(38). …”
Section: Phenotypic Characteristicssupporting
confidence: 57%
“…The GC content of the DNA ranges from 47.5 to 67.0 mol%. Descriptions of each genus and species have been reported previously (1,7,8,10,17,18,21,25,26,33,34,(36)(37)(38). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some species are opportunistically pathogenic to humans, where they can cause meningitis, septicaemia, bacteremia, peritonitis and wound infection (Yabuuchi et al, 1990). Non-phytopathogenic sphingomonads, such as Sphingomonas rosa, S. pruni, S. asaccharolytica and S. mali, were reported to be associated with plants (Takeuchi et al, 1995). In addition, large populations of sphingomonads were found living epiphytically on 26 plant species belonging to 11 families (Kim et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…in PY medium (Takeuchi et al, 1995). Bacterial DNA extraction, PCR with repetitive extragenic palindromic (REP) and enterobacterial repetitive intergenic consensus (ERIC) primers and DNA separation were carried out according to the procedures described by Rademaker & de Bruijn (1997).…”
Section: Rep-pcrmentioning
confidence: 99%